Factors related to Post Traumatic Stress Symptoms in Indonesian adults during quarantine of the COVID-19 pandemic - Evangelista, Nadya Nathalia; Wijovi, Felix; Orlin, Sisilia; Angelina, Stella; Halim, Devina Adella; Jodhinata, Claudia; Hamdoyo, Audrey; Cipta, Darien Alfa; Kurniawan, Andree; Lugito, Nata Pratama Hardjo (YCAB Publisher & IAKMI SULTRA, 2022)
Background: COVID-19 is an unprecedented public health event. It started from Wuhan, China, in late December of 2019 and later spread worldwide. During the pandemic, negative impacts on mental health were found in all groups, including adults of their productive age. Objective: This study aimed to search for factors related to Post Traumatic Stress Symptoms (PTSS) during the quarantine due to the COVID-19 pandemic in Indonesia, specifically about the demographic background of respondents and its relation to PTSS. Methods: This study employed a cross-sectional design involving 257 Indonesian adults aged 26-67 years from 26 out of 34 provinces in Indonesia. The questionnaire used in this study consists of demographic questions and an Indonesian version of the Impact of Event Scale-Revised (IESR). The questionnaire was distributed through a link attached to the social media platform from 17 September to 5 October 2020. Data were analyzed using t-test, one-way ANOVA, and multiple linear regression using SPSS 25.0. Results: The data analysis showed a significant relationship between age and mean IES-R score during quarantine time in Indonesia (p-value 0.001). Other demographic factors such as gender, education level, marital status, work from home, income during the pandemic, and pandemic effects to income showed no significant relation to the IES-R score of the respondents. Adults aged 25-44 years old tend to have higher IES-R scores than those aged 45-64 and 65+ years old. Conclusion: Age was related to the IES-R score, while the other five independent variables included in the linear regression analysis were found to be confounders in this study.